Long-Lasting Increased Risk of Human Papillomavirus–Related Carcinomas and Premalignancies After Cervical Intraepithelial Neoplasia Grade 3: A Population-Based Cohort Study - Ebisch, Renée M.F.; Rutten, Dominiek W.E.; IntHout, Joanna; Melchers, Willem J.G.; Massuger, Leon F.A.G.; Bulten, Johan; Bekkers, Ruud L.M.; Siebers, Albert G. (Journal of clinical oncology, 2017)
Purpose The aim of this study was to determine the risk of human papillomavirus (HPV)-related carcinomas and premalignancies in women diagnosed with cervical intraepithelial neoplasia grade 3 (CIN3). Knowledge of this risk is important to preventing the development and progression of other HPV-related premalignancies and carcinomas, by considering prophylactic HPV vaccination and/or by paying increased attention to other HPV-related carcinomas and premalignancies when CIN3 is identified. Methods Women diagnosed with a CIN3 between 1990 and 2010 were identified from the Dutch nationwide registry of histopathology and cytopathology (PALGA) and matched with a control group of women without CIN3. Subsequently, all cases of high-risk (hr) HPV-associated high-grade lesions and carcinomas in the anogenital region and oropharynx between 1990 and 2015 were extracted. Incidence rate ratios were estimated for carcinomas and premalignancies of the vulva, vagina, anus, and oropharynx. Results A total of 178,036 women were identified: 89,018 with a previous diagnosis of CIN3 and 89,018 matched control subjects without a history of CIN3. Women with a history of CIN3 showed increased risk of HPV-related carcinomas and premalignancies, with incidence rate ratios of 3.85 (95% CI, 2.32 to 6.37) for anal cancer, 6.68 (95% CI, 3.64 to 12.25) for anal intraepithelial neoplasia grade 3, 4.97 (95% CI, 3.26 to 7.57) for vulvar cancer, 13.66 (93% CI, 9.69 to 19.25) for vulvar intraepithelial neoplasia grade 3, 86.08 (95% CI, 11.98 to 618.08) for vaginal cancer, 25.65 (95% CI, 10.50 to 62.69) for vaginal intraepithelial neoplasia grade 3, and 5.51 (95% CI, 1.22 to 24.84) for oropharyngeal cancer. This risk remained significantly increased, even after long-term follow-up of up to 20 years. Conclusion This population-based study shows a long-lasting increased risk for HPV-related carcinomas and premalignancies of the anogenital and oropharyngeal region after a CIN3 diagnosis. Studies that investigate methods to prevent this increased risk in this group of patients, such as intensified screening or vaccination, are warranted.